Peningkatan Produksi Pangan melalui Sistem Integrasi Teknologi Aquaponics-Recirculating Aquaculture System (A-RAS) pada Budidaya Ikan Lele di Desa Kaliuntu Kabupaten Tuban - Yogita Ayu Dwi Susanti; Zulkisam Pramudia; Abdul Azis Amin; Lutfi Ni’matus Salamah; Adi Tiya Yanuar; Andi Kurniawan (Rekayasa, 2021)
Aquaponics-Recirculation Aquaculture System (A-RAS) technology combines recirculation systems in aquaculture with aquaponics technology. A-RAS technology can reduce water use in the aquaculture system and maintain water quality to fulfill aquaculture standards. The application of this system makes pond water that has been used for fish farming can be reused. This research used a descriptive analysis method to analyze A-RAS's application to improve food production through A-RAS in Kaliuntu, Tuban, East Java. This study's results showed that temperature during the study ranged from 27.5-30 °C, pH value ranged from 6.8-8.7, and the dissolved oxygen was around 3.1 mg/l. The content of nitrate, nitrite, and ammonia in the A-RAS technology was around 12.5 mg/l, 0-0.5 mg/l, and 0.003-0.09 mg/l, respectively. The application of A-RAS technology can increase the capacity and quality of the harvest of catfish cultivation. Harvest capacity increased from 100 kg to 180-190 kg / pond, the Food Convention Ratio (FCR) decreased from less than 1.0 to 0.705 and the Survival Rate (SR) increased from less than 75% to more than 95%. The results showed that the application of A-RAS technology could increase food production in Kaliuntu Village, Tuban Regency.